2017
DOI: 10.1158/1078-0432.ccr-17-0070
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Genetic Aberrations in the CDK4 Pathway in Acral Melanoma Indicate the Potential for CDK4/6 Inhibitors in Targeted Therapy

Abstract: Purpose: Effective therapies for the majority of metastatic acral melanoma patients have not been established. Thus, we investigated genetic aberrations of CDK4 pathway in acral melanoma and evaluated the efficacy of CDK4/6 inhibitors in targeted therapy of acral melanoma.Experimental Design: A total of 514 primary acral melanoma samples were examined for the copy number variations (CNV) of CDK4 pathway-related genes, including Cdk4, Ccnd1, and P16 INK4a , by QuantiGenePlex DNA Assay. The sensitivity of establ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 42 publications
7
97
2
Order By: Relevance
“…A study of 514 primary AM samples showed that the overall frequency of at least one aberration in CDK4, CCND1 or P16 INK4a was 82.7%. In this study, AM cell lines and patient-derived xenografts containing cyclin dependent kinase 4 (CDK4) pathway aberrations were sensitive to CDK4/6 inhibitors [105] and clinical studies are anticipated (NCT03454919). There are other, infrequently altered genes identified by AM sequencing studies; for example, mutations of MAP2K2 and loss of ARID2 [44].…”
Section: Am: Numerous Copy Number Changes and Low Point Mutation Burdenmentioning
confidence: 99%
“…A study of 514 primary AM samples showed that the overall frequency of at least one aberration in CDK4, CCND1 or P16 INK4a was 82.7%. In this study, AM cell lines and patient-derived xenografts containing cyclin dependent kinase 4 (CDK4) pathway aberrations were sensitive to CDK4/6 inhibitors [105] and clinical studies are anticipated (NCT03454919). There are other, infrequently altered genes identified by AM sequencing studies; for example, mutations of MAP2K2 and loss of ARID2 [44].…”
Section: Am: Numerous Copy Number Changes and Low Point Mutation Burdenmentioning
confidence: 99%
“…However, acral melanoma has not been related to the melanoma predisposition gene [11]. Oncogenomic studies indicate that somatic CNV of some genes is involved in melanoma progressions, such as mutated gene amplifications in CCND1, CDK4, and TERT [6,[12][13][14], of which the CNV status also has been reported in Chinese melanomas [14,15]. Accurate classification of the spectra of mutational changes in melanoma may facilitate the development of disease-associated biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on interactions between the drugs and key modules, we found eight small molecular agents (benzamidine, L-glutamine, zinc, XL844, AT7519, AT9283, alvocidib, and nelarabine) that could target LOI. AT7519 and alvocidib, a cyclin-dependent kinase inhibitor, have been reported to target CDK1 and thus proposed to have anticancer effects [31][32][33][34][35]. XL844 is a specific inhibitor of checkpoint kinase-1 and -2 and prevents the formation of a normal mitotic spindle; it can reportedly effectively sensitize cancer cells to induce cell cycle arrest [36].…”
Section: Discussionmentioning
confidence: 99%